Association Between Physical Fitness and Anxiety in Children: A Moderated Mediation Model of Agility and Resilience - Li, Yansong; Xia, Xue; Meng, Fanying; Zhang, Chunhua (Frontiers in Public Health, 2020)
Background: Anxiety is one of the most prevalent mental health problems in children. Although physical fitness as a predictor of mental health, the mechanisms underlying any association between physical fitness and anxiety in children have been understudied. Thus, the aim of the present study was to determine whether an association exists between physical fitness and anxiety and to explore the roles of agility and resilience in such an association. Methods: This cross-sectional study investigated 269 children aged 7 to 12 years from three public primary schools in Shanghai (China). Physical fitness and agility were objectively measured, and resilience and anxiety were assessed using self-reported questionnaires. The moderated mediation model was examined using the SPSS PROCESS macro, in which the moderator variable was agility, and the mediator variable was resilience. Results: Physical fitness was inversely associated with anxiety. Resilience partially and indirectly mediated this association, and agility moderated the association between physical fitness and resilience. Physical fitness had a greater impact on resilience in children with higher agility levels. Conclusions: Agility moderated the mediation of resilience on the indirect, inverse association between physical fitness and anxiety; thus, incorporating methods to develop agility and resilience may lead to better outcomes for physical fitness programs designed to prevent or alleviate anxiety in children.